The taxonomic significance of leaf micromorphology in the Genus Melastoma L. (Melastomataceae) - Noorma Wati Haron,; Nordiyanah Anuar,; Rubashiny Veeramohan, (Universiti Kebangsaan Malaysia, 2015)
A comparative leaf micromorphological study of Melastoma malabathricum, M. malabathricum var. alba and M. sanguineum (Melastomataceae) was carried out by scanning electron microscope. Characters such as epidermal cell shape, trichomes and stomatal type and distribution were observed. Non-glandular trichomes are present in all species examined. The stomata are all of paracytic type and dispersed randomly over the whole abaxial surface. The patterns of surface sculpturing and outer stomatal rim are unique in all the species examined. Leaf micromorphology has significant taxonomic value in the genus Melastoma and the present study has added some new taxonomic information for the genus Melastoma.